A novel start‐loss mutation of the SH2B3 gene in a family with myeloproliferative neoplasms. Issue 5 (21st May 2022) - Beghini, Alessandro; Leuzzi, Livia; Abazari, Nazanin; Bossi, Luca E.; Guido, Valentina; Trojani, Alessandra; Cairoli, Roberto
Abstract: The ever‐increasing advances in high‐throughput sequencing have broadened our understanding of the genetic pathogenesis of Philadelphia‐negative myeloproliferative neoplasms (MPNs). Convergent studies have shown that MPN driver mutations associate with additional mutations found in genes coding for negative regulators of the JAK/STAT signaling, including the SH2B3 (SH2B‐adaptor protein 3, also known as LNK ). Here, we describe a novel heterozygous start‐loss mutation of the SH2B3 gene (c.3G>A, SH2B3 M? ) in a consanguineous family characterized by recurrent early onset of JAK2 V617F ‐positive MPNs. The model represented by this pedigree suggests that the SH2B3 could be a predisposing mutation that facilitates the acquisition of driver mutations.